IL-2, IL-4, IFN-γ or TNF-α enhances BAFF-stimulated cell viability and survival by activating Erk1/2 and S6K1 pathways in neoplastic B-lymphoid cells. (August 2016) - Gui, Lin; Zeng, Qingyu; Xu, Zhigang; Zhang, Hai; Qin, Shanshan; Liu, Chunxiao; Xu, Chong; Qian, Zhou; Zhang, Shuangquan; Huang, Shile; Chen, Long
Highlights: IL-2/IL-4/IFN-γ/TNF-α reinforces BAFF-stimulated viability/survival in neoplastic B-lymphoid cells. IL-2/IL-4/IFN-γ/TNF-α enhances BAFF-stimulated B-cell viability/survival by activating Erk1/2 and S6K1 pathways. Manipulating IL-2/IL-4/IFN-γ/TNF-α level or blocking Erk1/2 or S6K1 may prevent BAFF-induced B-cell malignancies. Abstract: B-cell activating factor of the TNF family (BAFF) has been documented to act as a critical factor in the development of aggressive B lymphocytes and autoimmune diseases. However, the effect of various cytokines on BAFF-elicited neoplastic B-lymphoid cells is not known. In this study, we exhibited that administration of human soluble BAFF (hsBAFF), IL-2, IL-4, IFN-γ, or TNF-α alone increased cell viability and survival in Raji cells concentration-dependently, yet a more robust viability/survival was seen in the cells co-treatment of IL-2, IL-4, IFN-γ, or TNF-α with hsBAFF, respectively. Further research revealed that both Erk1/2 and S6K1 signaling pathways were essential for IL-2, IL-4, IFN-γ, or TNF-α enhancement of the viability/survival in the hsBAFF-stimulated cells, as inhibition of Erk1/2 with U0126 or down-regulation of Erk1/2, or blockage of S6K1 with rapamycin or silencing S6K1, or silencing S6K1/Erk1/2, respectively, reduced the cell viability/survival in the cells treated with/without hsBAFF ± IL-2, IL-4, IFN-γ, or TNF-α. These findings indicate that IL-2, IL-4, IFN-γ or TNF-α enhances BAFF-stimulated cell viability/survival by activating Erk1/2 and S6K1 signaling in neoplastic B-lymphoid cells. Our data suggest that modulation of IL-2, IL-4, IFN-γ and/or TNF-α levels, or inhibitors of Erk1/2 or S6K1 may be a new approach to prevent BAFF-induced aggressive B-cell malignancies.